Implementasi Tawakal dan Sabar pada Mantan Pecandu Narkoba dalam Menghadapi Stigma Sosial - Riska Nur Hanifah; Isnanita Noviya Andriyani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to explore the implementation of the concept of tawakal and sabar in former drug addicts in dealing with social stigma. The method used is qualitative with a phenomenological approach, involving three main subjects who have undergone rehabilitation and reintegration for one year and three supporting subjects. Data were collected through interviews and non-participatory observations, then analyzed by data reduction, presentation, and drawing conclusions through source triangulation. The results of the study showed that the subjects implemented sabar and tawakal in real terms. The aspect of sabar is seen in the steadfastness of worship, self-control, acceptance of destiny, positive thinking, and holding back complaints. While the tawakal aspect includes belief in Allah's provisions, maximum effort, dependence on Him, and pleasure in the results.